162k views
0 votes
Evaluate the expression below when x = -1. 2x2 - 5 x + 9 A. -7 8 B. -3 8 C. -1 8 D. -1

User Andigor
by
6.2k points

2 Answers

2 votes

Answer:

B -3/8

Explanation:

Because if x = -1 than it wou;d be

2(-1^2) − 5 = 2(1) -5 = 2-5 = -3

______________________________________

-1 + 9 = 8

User SyntaxError
by
6.0k points
3 votes

Answer:


Explanation:

Given,

x=-1

And the expression is-


2x^(2) -5x+9

Plugging in x=-1 we get


2x^(2) -5x+9

=
2(-1)^(2) -5(-1)+9

=2(1)+5+9

=2+14

=16

Answer should be 16 here.

Could you write the expression again please?

User Meeeee
by
6.0k points